Estrategias competitivas y su incidencia en el desarrollo de los productos financieros de la Cooperativa de Ahorro y Crédito Salinas Limitada, cantón Guaranda, provincia Bolívar, año 2019 - Cabezas Garzón, Victoria Fernanda (2020)
The research work is aimed at establishing the incidence of competitive strategies in the financial products of the Salinas Limitada Savings and Credit Cooperative, for which an analysis is made of the current situation of the financial products offered by the institution, the degree of compliance and satisfaction of these products on the needs of the partners, who when seeing the benefits are oriented to acquire or not acquire some type of financial product, depending largely on the way in which they are served by the members that make up the cooperative and the facility they have to access the requested financial product. Through the questionnaire applied to the members of the cooperative, it was found that they feel motivated to remain part of the institution because of the level of security it provides, both in the investments they wish to make or in the financial products they acquire, however argue that when accessing these products there is a delay in the processes of analysis of the documentation and requirement of many requirements, which sometimes generates that they do not wish to purchase the product; likewise, in the survey applied to the human talent of the cooperative, the commitment of the personnel in their work and the capacity they have to carry out their work is observed, where they consider that the application of competitive strategies will allow a growth in both the number of members , as well as in the institutional and therefore in an economic increase of the institution. Keywords: competitive strategies, financial products, development